Pre-Service Teachers’ Views of the Value of Cooperative Learning: How Can it Shape 21st-Century Skills? - Salvador-Garcia, Celina; Sanahuja Ribés, Aida (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Teacher education should provide pre-service teachers with the opportunity to use pedagogical approaches aligning with 21st-century skills, such as cooperative learning. This present, mixed-methods study aims to examine how cooperative learning may promote (or not) the development of the abilities that are needed for this era (i.e., collaboration, creativity, interest, engagement, and self-regulation), according to the participant pre-service teachers who attended a general-didactics course, completed a survey, and carried out a SWOT analysis. The quantitative results show that each of the 21st-century skills was developed, but to a different extent. The qualitative data, along with its integration with the quantitative data, provided a more comprehensive understanding of how and why each of the aforementioned proficiencies was developed, either confirming, or further explaining, the quantitative results. In conclusion, cooperative learning may foster the development of 21st-century skills, which are essential in the pursuit of quality education. Although no claims are made regarding the generalization of the findings, this study supports the idea that integrating cooperative learning in teacher education may promote relevant abilities and competencies among pre-service teachers, while providing them with experiences that may shape their future teaching practices.